Pengaruh Kompensasi dan Lingkungan Kerja terhadap Kinerja Pegawai Bank Intan Jabar (BIJ) Garut - Tinneke Hermina (Jurnal Wacana Ekonomi, 2016)
This study aims to determine the compensation and work environment on the performance of employees of Bank Intan Jabar (BIJ) Garut. The research method used is descriptive method with survey techniques. The population in this study were 104 employees of Bank Intan Jabar (BIJ) Garut. Sampling using the Slovin technique, in order to obtain a sample size of 83 samples. Data analysis techniques to answer the research hypothesis using statistical analysis with multiple regression analysis models. Testing of the hypothesis shows that there is a significant compensation effect on the employee performance of Bank Intan Jabar (BIJ) Garut which is shown from the partial test results of the partial correlation coefficient of 0.445 so that r2 is (0.445) 2 = 0.1980 or 19.80%. there is a significant work environment influence on the employee performance of Bank Intan Jabar (BIJ) Garut, which is shown from the partial test results of the partial correlation coefficient, which is 0.371 so that r2 is (0.371) 2 = 0.1376 or 13.76%, and there are the significant effect of compensation and work environment on the performance of employees of Bank Intan Jabar (BIJ) Garut, which is equal to 0.434 or 43.40%.